A fine line between stupid and clever : the story of Spinal Tap - Reiner, Rob; McKean, Michael; Shearer, Harry, 1943-; Guest, Christopher; Kamp, David (Gallery Books, 2025)
An inside look at the creation, legacy and cultural impact of the groundbreaking mockumentary comedy This Is Spinal Tap features behind-the-scenes stories, iconic quotes and rare memorabilia from the fictional band that became a real rock phenomenon.